A Fast-Dynamic Response Control Strategy for Power Supply Unit of SAR Satellites. Issue 1 (November 2020) - Zhang, Xiaofeng; Li, Haijin; Li, Jiannong; Zang, Jie; Gu, Yu; Zhang, Donglai
Abstract: For the power supply of spacecraft, the dynamic response is a key requirement for converters. Especially for power supplies of SAR or other pulse power supplies, the transient of load is fast and the output current is high, it is very difficult to guarantee the output voltage in the required range. The ECSS-E_ST-20C has provided a standard for the power quality of power supply for spacecraft. In this paper, a fast-dynamic response control strategy for buck converters is proposed. The proposed strategy does not increase the output capacitance, and increases the dynamic response of the converter. In the proposed strategy, the linear control and non-linear control are combined. The linear control operates in the steady state, while the non-linear control operates in the transit state. Finally, the proposed strategy is verified by simulations and experiments.